Implementasi Persetujuan TRIPs dalam Undang-Undang Hak Cipta Indonesia - Nandang Sutrisno (Jurnal Hukum IUS QUIA IUSTUM, 1999)
The enactment of Copy Rights Law 1997 No. 12 has been the effort of Indonesia to harmonize intellectual property rights laws with the Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPs). The Law embodies some substantial changes so that they have been relevantand significan tas the implementation of TRIPs. The changes have oriented to wardnew norms, hig her standards and strict law enforcement. The mostimportantthing, how ever, hasbeen the social significant of the law in order to beeff ective.